Performance adaptations to short-term sled towing and sprint training - Alcaraz, P. E.; Elvira, J. L. L.; Palao, J. M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The use of resisted sprinting techniques is common both in athletics and in a variety of sports (Cronin and Hansen, 2006). However, previous research has focused in studying the performance when applying these methods on untrained subjects (Zafeiridis et al., 2005; Kristensen et al., 2006). Considering that the magnitudes and time courses of the neural adaptations in the neuromuscular system in elite athletes may differ from those adaptations reported for untrained athletes (Hakkinen et al., 1987), the results from those papers may not be representative of the experienced subjects. Therefore, the aim of the study was to examine the effects of resisted and unloaded sprint training programs on acceleration, transition and maximum speed performance on experienced athletes.